STUDI KEANEKARAGAMAN MIKROALGA DI SUNGAI MARGASATWA RAGUNAN SEKITAR KANDANG BUAYA - Setyani, Anisa Intan; Sari, Deva Dewiyana; Permatasari, Maulida Azzra; Izat, Muhammad; Bintang, Sekar; Suryanda, Ade; Azrai, Eka Putri (Universitas Pakuan, 2024)
Microalgae are microscopic unicellular organisms that have varying sizes, shapes, and types, have photosynthetic pigments, are photoautotrophic, and are found in aquatic environments. Microalgae have certain limits of tolerance to water chemical physics factors. The presence of microalgae in water can be used as an indicator of the state of the water. This study aims to identify the diversity of microalgae as an indicator of the water quality present in the river around the Ragunan Margasatwa crocodile cage. Sampling was done in the Ragunan Margasatwa Park river near the crocodile cage. Samples of macroalgae are visually identified and include morphology, color, shape, and other characteristics. Based on the observations, it can be concluded that the river ecosystems around the crocodile cages are under low ecosystem pressure. The diversity index generally has a range of values between 1.5 and 4, and lower values reflect increasing ecosystem instability. The lowest microalgae density was found at station 1, which is 120 ind/ml. Individuals with the highest density at station 2, the species Aphanothece sp. with a density value of 293.3 ind/mL.